91.5k views
3 votes
Which procedure justifies whether Negative 3 x (5 minus 4) + 3 (x minus 6) is equivalent to Negative 12 x minus 6? The expressions are not equivalent because Negative 3 (2) (5 minus 4) + 3 (2 minus 6) = negative 18 and Negative 12 (2) minus 6 = negative 30. The expressions are not equivalent because Negative 3 (2) (5 minus 4) + 3 (2 minus 6) = negative 18 and Negative 12 (3) minus 6 = negative 42. The expressions are equivalent because Negative 3 (2) (5 minus 4) + 3 (2 minus 6) = negative 18 and Negative 12 (negative 2) minus 6 = 18. The expressions are equivalent because Negative 3 (2) (5 minus 4) + 3 (2 minus 6) = negative 18 and Negative 12 (1) minus 6 = negative 18.

2 Answers

4 votes

The expressions are not equivalent because -3(2)(5-4)+3(2-6)=-18 and -12(2)-6=-30

So, It's A

User Jan Gerlinger
by
6.6k points
3 votes

Answer:

The expressions are not equivalent because -3(2)(5-4)+3(2-6)=-18 and -12(2)-6=-30

Explanation:

Two expressions are said to be equal if after a number is substituted to the expression, they produce the same result (that is they have the same value).

To determine whether -3x(5-4)+3(x-6) is equivalent to -12x-6, we have to substitute the same number to the expression and see if it produces the same result.

Substituting 2 to the first expression gives:

-3×2(5-4) + 3(2 - 6) = -6 - 12 = -18

Substituting 2 to the second expression gives:

-12(2) - 6 = -24 - 6 = -30

Since -3×2(5-4) + 3(2 - 6) = -6 - 12 = -18 and -12(2) - 6 = -24 - 6 = -30, the expressions are not equivalent because they do not produce the same result.

User Virgil
by
6.0k points